2019
DOI: 10.3390/ijms20153672
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione Metabolism in Renal Cell Carcinoma Progression and Implications for Therapies

Abstract: A significantly increased level of the reactive oxygen species (ROS) scavenger glutathione (GSH) has been identified as a hallmark of renal cell carcinoma (RCC). The proposed mechanism for increased GSH levels is to counteract damaging ROS to sustain the viability and growth of the malignancy. Here, we review the current knowledge about the three main RCC subtypes, namely clear cell RCC (ccRCC), papillary RCC (pRCC), and chromophobe RCC (chRCC), at the genetic, transcript, protein, and metabolite level and hig… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
60
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(61 citation statements)
references
References 128 publications
(204 reference statements)
1
60
0
Order By: Relevance
“…This suggests possible alternative roles for CI mutations in OXPHOS or, as-yet unknown, compensatory mechanisms leading to increased transcript levels of OXPHOS-related factors. It was recently reported that chRCC and RO have elevated levels of GSH (24)(25)(26)(27)(28), which is a novel hallmark of all RCCs and a potential therapeutic target (29). Enhanced GSH biosynthesis in RO is presumed to be an adaptive event resulting from loss-of-function mutations in CI subunits (24,25).…”
Section: Introductionmentioning
confidence: 99%
“…This suggests possible alternative roles for CI mutations in OXPHOS or, as-yet unknown, compensatory mechanisms leading to increased transcript levels of OXPHOS-related factors. It was recently reported that chRCC and RO have elevated levels of GSH (24)(25)(26)(27)(28), which is a novel hallmark of all RCCs and a potential therapeutic target (29). Enhanced GSH biosynthesis in RO is presumed to be an adaptive event resulting from loss-of-function mutations in CI subunits (24,25).…”
Section: Introductionmentioning
confidence: 99%
“…The resistance shown by these cells may be related to their high concentration of intracellular glutathione (GSH) . Renal carcinoma cells are known for producing a high concentration of intracellular glutathione (GSH) . This antioxidant protects cells from toxic effects of reactive species of oxygen (ROS) and elimination of xenobiotics.…”
Section: Introductionmentioning
confidence: 99%
“…Clear‐cell renal carcinoma is also considered a hypervascular tumor due to inactivation of the suppressor von Hippel Lindau gene that triggers the induction of proangiogenic factors, facilitating metastasis . All these factors make renal carcinoma an invasive and aggressive tumor . Herein, the focus was on some mechanisms responsible for the anticancer activity of many anticancer agents.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations